Comparative physiological and transcriptional analysis of weak organic acid stress in Bacillus subtilis. (February 2015) - Ter Beek, Alexander; Wijman, Janneke G.E.; Zakrzewska, Anna; Orij, Rick; Smits, Gertien J.; Brul, Stanley
Abstract: The advent of 'omics' techniques bears significant potential for the assessment of the microbiological stability of foods. This requires the integration of molecular data with their implication for cellular physiology. Here we performed a comparative physiological and transcriptional analysis of Bacillus subtilis stressed with three different weak organic acids: the commonly used food preservatives sorbic- and acetic-acid, plus the well-known uncoupler carbonyl cyanide-m-chlorophenyl hydrazone (CCCP). The concentration of each compound needed to cause a similar reduction of the growth rate negatively correlated with their membrane solubility, and positively with the concentration of undissociated acid. Intracellular acidification was demonstrated by expressing a pH-sensitive GFP derivative. The largest drop in intracellular pH was observed in CCCP-stressed cells and was accompanied by the transcriptional induction of the general stress response (GSR) and SigM regulon, responses known to be induced by acidification. The GSR was induced by acetate, but not by sorbate in mildly-stressed cells. Microarray analysis further revealed that all three acids activate transcriptional programs normally seen upon nutrient limitation and cause diverse responses indicative of an adaptation of the cell envelope. Based on the responses observed and the utilized pH measurements, the inhibitory effect of sorbic acid seems to be more focused on the cell membrane than that of acetic acid or CCCP. Highlights: Effect of weak organic acids depends on undissociated acid and membrane solubility. Intracellular acidification was demonstrated using a pH-sensitive GFP (pHluorin). Weak organic acids induce responses normally seen upon nutrient limitation. Weak acids induce (distinct) responses indicative of cell envelope adaptations.